Evaluation of composting control parameters (oxygenation and C/N ratio) from household waste in Neiva, Huila - Giraldo Murcia, Julián Alejandro
Organic solid waste is a source of raw material for the production of soil conditioners that, thanks to a decomposition and composting process, are used in small-scale food production. However, the production process depends on the proper handling and disposal of waste because of the variations in the different stages of the composting process. The objective of this study is to evaluate the parameters of compostingcontrol (oxygenation and C / N ratio) from kitchen waste previously balanced in itsbromatological content, produced in residential units in the city of Neiva. A survey was conducted in a residential community in the city of Neiva, Huila on the disposal of household waste, subsequently, three types of composting were evaluated based on oxygenation and the carbon-nitrogen (C / N) ratio of the pile. In the statisticalanalysis, the temperature factor (dependent variable) vs each of the treatments (Tr1,Tr2 and Tr3) were considered until their decomposition was completed after 75 days ofanalysis. Treatments with an initial C / N ratio between 25 and 30 presented highertemperatures and, therefore, proved to be the most beneficial to the sanitizationprocess useful in reducing pathogenic microorganisms in the compost. In addition,the compost matured in less time with the horizontal rotary biodigester system.